Enhancing Learning Achievement in Mathematics Subject on Addition and Subtraction of Numbers within 1,000 through Poki Games for Grade 2 Students - ชมภูษา กิตติยา; อุส่าห์รัมย์ กัญญมาส; กาญจนเรืองรัตน์ ณัฐพงศ์; สุวรรณวงศ์ ศิริลักษณ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) compare the learning achievement in mathematics subject on addition and subtraction of numbers within 1,000 of grade 2 students before and after being taught using the Poki game-based learning approach, and 2) compare the learning achievement in mathematics on addition and subtraction of numbers within 1,000 of grade 2 students after being taught using the Poki game with a 70 percent criterion. The sample group consisted of 34 grade 2 students from class 2/3 at Wat Bangpla (Samutwanaratbamrung) School, selected by cluster random sampling. The research instruments included five lesson plans using Poki games, which had an appropriateness average between 3.53 - 4.00, which was very appropriate. Additionally, a 20-item achievement test with a difficulty index between 0.23 - 0.80, a discrimination index between 0.43 - 0.60, and a reliability value of 0.75. The statistics used in data analysis were dependent t-test and one sample t-test. The research findings revealed that 1) the students who received learning management using the Poki had higher learning achievement scores after learning than before learning, with statistical significance at the .05 level, and 2) the students who received learning management using Poki game had learning achievement scores after learning at 79.56 percent, which was significantly higher than the 70 percent criterion at the statistical level of .05.